1997
DOI: 10.1161/01.cir.96.9.2782
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Infusion of Prostacyclin Normalizes Plasma Markers of Endothelial Cell Injury and Platelet Aggregation in Primary Pulmonary Hypertension

Abstract: Alterations in the coagulation system may contribute to the pathogenesis of PPH; the normalization of these endothelial markers concomitant with improvement in hemodynamic parameters with long-term PGI2 suggests that long-term PGI2 remodels the pulmonary vascular bed with subsequent decreases in endothelial cell injury and hypercoagulability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
2
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 144 publications
(81 citation statements)
references
References 11 publications
1
77
2
1
Order By: Relevance
“…The greater endothelial eNOS expression is more likely to be due to the epoprostenol therapy than to the activity of the ETB receptors. Long-term epoprostenol given as monotherapy has been shown to improve endothelial function, as judged by an improvement in the net balance between pulmonary ET-1 clearance and release and the coagulation profile [34]. In the present study, it is obviously impossible to dissect how the administration of bosentan and/ or prostacyclin might have influenced endothelial function.…”
Section: Discussionmentioning
confidence: 71%
“…The greater endothelial eNOS expression is more likely to be due to the epoprostenol therapy than to the activity of the ETB receptors. Long-term epoprostenol given as monotherapy has been shown to improve endothelial function, as judged by an improvement in the net balance between pulmonary ET-1 clearance and release and the coagulation profile [34]. In the present study, it is obviously impossible to dissect how the administration of bosentan and/ or prostacyclin might have influenced endothelial function.…”
Section: Discussionmentioning
confidence: 71%
“…30 Previous studies have also identified other nonvasodilator actions of epoprostenol in PPH, including improvement in coagulation and platelet function. 31,32 Future studies drawing on the results of these and the present study will shed light on the interactions between vasoactive and pro-or antimitogenic mediators in PPH, advancing our understanding of the mechanisms of action, other than vasodilatory, of therapies for the disease. …”
Section: Discussionmentioning
confidence: 74%
“…Elevated plasma vWF and its antigen (vWF:Ag) have been used as markers of endothelial cell injury in a variety of conditions. Levels of vWF:Ag are elevated in PH [82,83] and baseline vWF:Ag correlates with the risk of death in the subsequent year [83]. In another study, vWF was also found to be elevated in severe PAH, and paralleled improvements in haemodynamics on prostacyclin therapy, although this was only in 10 patients [84].…”
Section: Plasma Von Willebrand Factormentioning
confidence: 96%